Simultaneous HPTLC Estimation of Simvastatin and Ezetimibe in Tablet Dosage Form. Issue 4 (2010) - Shrestha, Bhupendra; Stephenrathinaraj, B.; Patel, Sita Sharan; Verma, N. K.; Mazumder, R.
Abstract : A method enabling the precise and quick simultaneous analysis of simvastatin and ezetimibe in tablet formulation by high performance thin layer chromatography has been presented. Samples of simvastatin and ezetimibe in organic solvents were separated on a plate coated with silica gel 60 F-254 and the chromatograms were developed using a mixture of chloroform and methanol (9.5: 0.5 %v/v). The method has a linearity range of 40-280 ng.mL -1 for both the drugs when scanned at 254 nm. The limit of detection and limit of quantitation was found to be 30 and 100 ng.band -1 respectively, for both the drugs. The mean percent recovery was found to be 100.65 and 101.55 for simvastatin and ezetimibe. The intra-day and inter-day precision studies were carried out with mean RSD of 0.88 and 1.27 for ezetimibe and 1.35 and 1.50 for simvastatin.